Author Correction: Activation of endothelial β-catenin signaling induces heart failure. Issue 1 (December 2018) - Nakagawa, Akito; Naito, Atsuhiko; Sumida, Tomokazu; Nomura, Seitaro; Shibamoto, Masato; Higo, Tomoaki; Okada, Katsuki; Sakai, Taku; Hashimoto, Akihito; Kuramoto, Yuki; Oka, Toru; Lee, Jong-Kook; et al.
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.